2020
DOI: 10.1177/1077559520925180
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Reminiscing Is Associated With Preschoolers’ Reports of Maltreatment During Forensic Interviews

Abstract: Children’s reports during forensic interviews regarding maltreatment allegations are often critical for legal processes and for guiding decisions regarding services for children and their families. Field research examining forensic interviews with children has identified a wide range in the amount of information children report to interviewers. Research examining associations between children’s forensic reports and their broader ecological and developmental contexts related to autobiographical memory would cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In such situations, parents understandably would be highly motivated to get to the bottom of their concerns. Admittedly, parents’ questioning style and children’s susceptibility to maternal bias may differ when centered on legally relevant events, though Lawson et al (2021) found that maternal reminiscing styles predicted children’s disclosure of maltreatment in forensic interviews. Below, in the final section, we conclude by further discussing the forensic implications of the parent–child studies and by offering several recommendations for forensic practice.…”
Section: Limitations Of Researchmentioning
confidence: 95%
“…In such situations, parents understandably would be highly motivated to get to the bottom of their concerns. Admittedly, parents’ questioning style and children’s susceptibility to maternal bias may differ when centered on legally relevant events, though Lawson et al (2021) found that maternal reminiscing styles predicted children’s disclosure of maltreatment in forensic interviews. Below, in the final section, we conclude by further discussing the forensic implications of the parent–child studies and by offering several recommendations for forensic practice.…”
Section: Limitations Of Researchmentioning
confidence: 95%
“…Maltreating mothers who discuss the past with their children in more detailed, coherent, and emotionally sensitive ways have children with better psychological adjustment (Valentino et al, 2022) and increased autobiographical memory skills (Valentino et al, 2021), including enhanced memory for abuse and neglect (Lawson, Jaeger, et al, 2021). However, relative to children with nonmaltreating mothers, children with maltreating mothers are less likely to experience the maternal support and scaffolding necessary to facilitate children’s memory and adjustment following sexual abuse (Salmon & Reese, 2015).…”
Section: Mother–child Conversations and Children’s Reports For Experi...mentioning
confidence: 99%
“…Maternal elaboration refers to maternal use of open-ended questions, closed-ended questions, and embellishment upon details (Nelson & Fivush, 2004). Maternal autonomy support refers to the extent to which mothers expand on topics introduced by children and encourage children to provide their own perspectives of events (Cleveland & Reese, 2005; Lawson, Jaeger, et al, 2021). Mothers can simultaneously vary in elaboration and autonomy support.…”
Section: Mother–child Conversations and Children’s Reports For Nonexp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research on conversation in child witness cases has primarily focused on what children remember from conversations with parents or perpetrators (e.g., Lawson & London, 2017; Lyon & Stolzenberg, 2014; Stolzenberg et al, 2018) or how parents shape their children’s subsequent memory reports (e.g., Klemfuss et al, 2016; Lawson et al, 2018, 2021; Poole & Lindsay, 2001; Principe et al, 2017). Far fewer studies have examined adults’ memory for conversations with children, but, as Principe and London (2022) note, collectively their findings are consistent with the broader literature on conversational memory which found that witnesses are more proficient at recalling a conversation’s gist (i.e., general representations of conversational content) than its verbatim content (e.g., the conversation’s structure; Brown-Schmidt & Benjamin, 2018; Davis & Friedman, 2007; Hirst & Echterhoff, 2012).…”
Section: The Challenge Of Fresh Complaint Testimonymentioning
confidence: 99%